Recurrent Cutibacterium acnes prosthetic valve endocarditis - Abdelhamid, Ahmed Ashraf (BMJ Case Rep, 2021)
A 29-year-old man with a history of congenital aortic stenosis and mechanical aortic valve replacement with previous Cutibacterium acnes prosthetic valve endocarditis (PVE) presented with a 2-week history of fevers and night sweats. Transoesophageal echocardiogram revealed a 0.6 cm×0.5 cm vegetation on the mechanical aortic valve. An anaerobic blood culture became positive for C. acnes 6 days after the blood cultures were obtained. He did not have any surgical intervention. He was successfully treated with 6 weeks of ceftriaxone, followed by chronic suppression with oral doxycycline. Despite its low virulence, a growing number of C. acnes PVE cases have been reported, owing to its biofilm production. When clinical suspicion is high, extending culture incubation duration beyond the standard 5 days might be helpful. Most cases are treated with surgical repair or replacement in conjunction with antibiotics, but medical therapy alone has been documented as being successful.